Β-Asarone modulate adipokines and attenuates high fat diet-induced metabolic abnormalities in Wistar rats. (January 2016) - Thakare, Malesh M.; Surana, Sanjay J.
Graphical abstract: Abstract: Here we investigated the effect of β-asarone on food preference and its therapeutic potential against high fat diet (HFD) induced obesity in rats. In food preference study, free access to HFD was given only for 4 h in addition to standard laboratory chow in rats and the preferential intake between chow and HFD was measured. For obesity induction, HFD was administered for 12 weeks and the HFD fed rats were treated with β-asarone in the last 4 weeks, starting from 9th week onwards. Food intake, body weight was measured biweekly. Glucose tolerance and the levels of glucose, lipids, free fatty acids, leptin, and adiponectin were assessed. HFD fed rats showed progressive increase in body weight and developed glucose intolerance and dyslipidemia. In addition, they showed increased adiposity and the disturbed pattern of adipokine levels In the food preference paradigm, β-asarone produced selective decrease in HFD intake in rats. In obese rats, β-asarone treatment not only reduced body weight but also prevented HFD-induced metabolic alterations, including glucose intolerance, dyslipidemia and adipokine imbalance. The observed beneficial effects of β-asarone appear due its ability to reduce intake of energy dense food by affecting food palatability, and to normalize the levels of leptin and adiponectin in rats. Overall, our results suggest that β-asarone is a novel candidate molecule with significant therapeutic potential in the management of obesity and associated abnormalities.